MKRN2 Physically Interacts with GLE1 to Regulate mRNA Export and Zebrafish Retinal Development - Eric J. Wolf (Cell Reports, 2020)
Summary: The mammalian mRNA nuclear export process is thought to terminate at the cytoplasmic face of the nuclear pore complex through ribonucleoprotein remodeling. We conduct a stringent affinity-purification mass-spectrometry-based screen of the physical interactions of human RNA-binding E3 ubiquitin ligases. The resulting protein-interaction network reveals interactions between the RNA-binding E3 ubiquitin ligase MKRN2 and GLE1, a DEAD-box helicase activator implicated in mRNA export termination. We assess MKRN2 epistasis with GLE1 in a zebrafish model. Morpholino-mediated knockdown or CRISPR/Cas9-based knockout of MKRN2 partially rescue retinal developmental defects seen upon GLE1 depletion, consistent with a functional association between GLE1 and MKRN2. Using ribonomic approaches, we show that MKRN2 binds selectively to the 3′ UTR of a diverse subset of mRNAs and that nuclear export of MKRN2-associated mRNAs is enhanced upon knockdown of MKRN2. Taken together, we suggest that MKRN2 interacts with GLE1 to selectively regulate mRNA nuclear export and retinal development.